Anthocyanins of Asian bird cherries (Prunus nepalensis L.): An untapped source for natural food colorants. Issue 11 (14th September 2022) - Ma, Bohan; Wang, Kaijie; Guo, Juntong; Zhu, Ge; Zhao, Xinghua; Zhao, Mengge; Yang, Xingbin; Shao, Hongjun
Abstract: Interest in the processing and application of natural anthocyanin pigments is intensifying. In this work, we developed a protocol for obtaining anthocyanins from wild Asian bird berries ( Prunus nepalensis L.) using ultrasound‐assisted extraction (UAE) and response surface methodology. The chemical profile, antioxidant activity, and co‐pigmentation of the anthocyanin extract were also investigated. The results showed that the maximum anthocyanin yield was achieved under optimal conditions of 60°C, 300 W ultrasonic power, and 30 min ultrasonic time. Using UHPLC‐ESI‐MS 2 analysis, two major anthocyanins and 19 other phenolics were identified in the anthocyanin extract, which displayed significant antioxidant potential in vitro. In addition, the color stability of the anthocyanin extract was thermodynamically improved by phenolic acids and organic acids where oxalic acid was the most effective co‐pigment. These results revealed that Asian bird berries anthocyanins could be effectively recovered by UAE, and further stabilized by co‐pigments. Novelty impact statement: The chemical instability of anthocyanins poses a significant challenge for their preparation and implementation as food colorants. In this study, the anthocyanins obtained from P. nepalensis L. fruits were modulated, for the first time, with the help of co‐pigments such as oxalic acid, citric acid, ascorbic acid, gallic acid, tannic acid, and pyrogallic acid. These results could open up the possibility of large‐scale applications of anthocyanins sourced from many uncultivated plants.